2009
DOI: 10.1080/15569520902995834
|View full text |Cite
|
Sign up to set email alerts
|

Ocular preservatives: associated risks and newer options

Abstract: Presence of a preservative in an ocular medication has often been considered a culprit in damaging the epithelium. However, the inclusion of a preservative is equally necessary, especially in multiple-dose containers, in order to protect against dangerous organisms accidentally gaining access during instillation. Benzalkonium chloride (BAK), chlorobutanol, chlorhexidine acetate (CHA), and phenylmercuric nitrate or acetate are some commonly used preservatives in eye preparations. New preservatives with a wide r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 41 publications
0
62
0
1
Order By: Relevance
“…Benzalkonium chloride (BAK) is one of the most potent preservatives and a component of most eye drops, (Kaur et al 2009) because of its strong beneficial effect on microbacterial protection and solvent. On the other hand, BAK induces cytotoxic effects on cultured keratoconjunctival epithelial cells (Burstein 1980;De Saint Jean et al 2000;Cha et al 2004;Guenoun et al 2005;Leung et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Benzalkonium chloride (BAK) is one of the most potent preservatives and a component of most eye drops, (Kaur et al 2009) because of its strong beneficial effect on microbacterial protection and solvent. On the other hand, BAK induces cytotoxic effects on cultured keratoconjunctival epithelial cells (Burstein 1980;De Saint Jean et al 2000;Cha et al 2004;Guenoun et al 2005;Leung et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Günümüzde antiglokomatöz ajanlar da dâhil olmak üzere, mevcut göz damlalarının %70'inin şişe içeriğinde prezervan madde olarak BAK mevcuttur. 10 Topikal solüsyonlardaki en sık kullanılan konsantrasyonu %0,01 olmakla birlikte, %0,004-0,02 arasında farklı uygulamaları da olabilmektedir. Bu maddenin antimikrobiyal özelliği deterjan etkisinden kaynaklanmaktadır.…”
Section: Discussionunclassified
“…Eliminating or reducing exposure to BAK in ophthalmic solutions improves tear film stability, reduces conjunctival hyperemia, and improves dry eye symptoms. 7,[13][14][15] The present study was undertaken to examine the efficacy, safety, tolerability of BAK-free travoprost ophthalmic solution compared with BAK-preserved travoprost. The study demonstrated that the IOP-lowering efficacy was equivalent between BAK-free travoprost 0.004% and BAK-preserved travoprost 0.004%.…”
Section: Discussionmentioning
confidence: 99%
“…The classification of normal, mild, moderate, or severe OSD was determined on a scale from 0 to 100. OSD severity was classified as follows: normal (0-12), mild (13)(14)(15)(16)(17)(18)(19)(20)(21)(22), moderate (23-32), and severe (33-00). Global Evaluation of Overall Tolerability (GEOT) was assessed at 12 weeks.…”
Section: Methodsmentioning
confidence: 99%